SEMANTIC ANALYSIS OF ENGLISH IDIOMS IN MONSTER, INC MOVIE - Syifa Nurhikmah Lestari; Nova Agus Mulia; Ririn Yusrini Mudawamah; Tatu Siti Rohbiah (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This study aimed to analyze the interpretation of English idioms in the Monsters, Inc movie through semantic and pragmasemantic approaches. The research addressed the issue that idiomatic expressions are difficult to understand literally without considering their contextual use. A descriptive qualitative method was employed, using documentation techniques by collecting data from the movie's transcript and subtitles, contextual meaning approaches from Leech and Palmer. The findings showed that the idioms in this film were mostly pure idioms, which convey non-literal meanings highly dependent on situational context. Idioms in the film functioned not only as linguistic elements but also as tools for expressing emotion, building character identity, and delivering humor. It was concluded that idiom comprehension in films can be enhanced through contextual interpretation. This study contributes to English language teaching by promoting the use of animated films as engaging and contextual learning media.